2014
DOI: 10.1172/jci71103
|View full text |Cite
|
Sign up to set email alerts
|

Excess PLAC8 promotes an unconventional ERK2-dependent EMT in colon cancer

Abstract: The epithelial-to-mesenchymal transition (EMT) transcriptional program is characterized by repression of E-cadherin (CDH1) and induction of N-cadherin (CDH2), and mesenchymal genes like vimentin (VIM). Placenta-specific 8 (PLAC8) has been implicated in colon cancer; however, how PLAC8 contributes to disease is unknown, and endogenous PLAC8 protein has not been studied. We analyzed zebrafish and human tissues and found that endogenous PLAC8 localizes to the apical domain of differentiated intestinal epithelium.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 85 publications
10
108
1
Order By: Relevance
“…Moreover, PLAC8 overexpression resulted in induction, rather than inhibition, of apoptosis in both primary and transformed human lymphocytes (11), and decreased PLAC8 expression was reported to be associated with oncogenesis in the liver (34). Further evidence for context-dependent differential roles of PLAC8 comes from a study by Li and colleagues (13), who demonstrated that PLAC8 overexpression caused decreased migration of mesenchymal cells in zebrafish embryos, while resulting in enhanced migration and features reminiscent of epithelial-to-mesenchymal transition in cultured colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PLAC8 overexpression resulted in induction, rather than inhibition, of apoptosis in both primary and transformed human lymphocytes (11), and decreased PLAC8 expression was reported to be associated with oncogenesis in the liver (34). Further evidence for context-dependent differential roles of PLAC8 comes from a study by Li and colleagues (13), who demonstrated that PLAC8 overexpression caused decreased migration of mesenchymal cells in zebrafish embryos, while resulting in enhanced migration and features reminiscent of epithelial-to-mesenchymal transition in cultured colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although evolutionarily highly conserved, the protein does not contain any known functional domains, and its molecular function remains enigmatic. Moreover, the cellular role of PLAC8 seems to be highly contextdependent, resulting in strongly variable, and sometimes contradictory, effects of PLAC8 modulation in different cell types, ranging from apoptosis protection in fibroblasts (10) versus apoptosis induction in human lymphocytes (11) to inhibition of cell differentiation in primary acute myeloid leukemia cells (12), and induction of epithelial-to-mesenchymal transition in cultured colon cancer cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in these genes, signaling pathways along with certain other pathways, including wnt/β-catenin, play essential roles in CRC progression (22)(23)(24)(25)(26). The correlation between ZFX and these genes and pathways in CRC progression requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Mutually exclusive phosphorylation patterns of the two canonical substrates of mTORC1 (S6K1 and 4E‐BP1) were observed in individual cells, large regions of most tumors, and in distinct cell lineages, demonstrating differential pathway activation. In the research setting, MxIF has also been applied to evaluate signaling pathway changes in mouse salivary glands,26 estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), and Ki67 colocalization in breast cancer,27 and other single‐cell analyses 28, 29…”
Section: Hyperplexed Fluorescence Measurements Of the Cellular And Sumentioning
confidence: 99%
“…Multiplex protein expression (4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37) …”
mentioning
confidence: 99%